The Locating Chromatic Number for Pizza Graphs - Surbakti, Nurul Maulida; Kartika, Dinda; Nasution, Hamidah; Dewi, Sri (Universitas PGRI Palembang, 2023)
The location chromatic number for a graph is an extension of the concepts of partition dimension and vertex coloring in a graph. The minimum number of colors required to perform location coloring in graph G is referred to as the location chromatic number of graph G. This research is a literature study that discusses the location chromatic number of the Pizza graph. The approach used to calculate the location-chromatic number of these graphs involves determining upper and lower bounds. The results obtained show that the location chromatic number of the pizza graph is 4 for n = 3 and n for ≥ 4.